THE EFFECT OF INQUIRY MODEL ON STUDENTS’ LEARNING OUTCOMES ON THE THEME OF “BENDA-BENDA DISEKITARKU” AT GRADE V SDN 076713 ZUZUNDRAO - Kariati Zai; Antonius Remigius Abi; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the effect of inquiry model on students’ learning outcomes on the theme “Benda-Benda Disekitarku” at grade V SDN 076713 Zuzundrao in the Academic Year 2019/2020. This study used inquiry model with a quantitative research type. The population was all fifth grade students of SDN 076713 Zuzundrao consisting of 3 classes. Then, the sample chosen was class V-A, which consisted of 30 students. The data were collected through a test containing 30 essay questions which were declared valid and reliable. The result of correlation obtained that rcount = 0.672 ≥ rtable = 0.361. This implied that there was a significant influence between inquiry model and learning outcomes. Furthermore, it was found that the average score of the students’ learning outcomes was 173.7. Then, the result of t test revealed that tcount = 4.786 while ttable = 1.701. Since tcount > ttable, Ho was rejected. It proved that there was a significant influence of inquiry model on the students’ learning outcomes on the theme of “Benda-Benda Disekitarku” at grade V SDN 076713 Zuzundrao in the Academic Year 2019/2020.